STUDI PERENCANAAN SPILLWAY MORNING GLORY PADA BENDUNG WAI WOKI KABUPATEN NGADA - PANJI PRAYOGA; Leonardus Setia Budi Wibowo; Muhammad Shofwan Donny Cahyono; Norman Ray (Program Studi Teknik Sipil Universitas Narotama, 2020)
The spillway construction is one of the components of a dam which has function to protect the dam from overtopping during a flood. Wai Woki’s dam is the object on this plan, it is planned to use the type of morning glory spillway. The spillway is a structure that is used to control the release of water flowing from the dam to the downstream areas, shaped tower / funnel which is very effective for dams that do not have sufficient space for the overflow of other spillway types. The planned dam has a period of 100 years with a watershed area of 38,25 km2 and length of the river 9,61 km as well as the daily rainfall data as much as 10 years. From the results of the study obtained that spillway top elevation is +120.00 MASL with maximum flood discharge 90,39 m3 / sec at an elevation of +121,25. The structure height 30 meters with the peak of diameter is 6 meters and a diameter of conduit is 4,5 meters. The lenght of the tunnel conduit is 212,065 meter. As well as the wall thickness of 0.40 meters with a reinforcement horizontal and vertical D24-150 mm. Keywords: morning glory spillway, pelimpah corong, spillway